أثر ممارسة عمليات إدارة المعرفة على قدرات الذكاء التنظيمي : دراسة ميدانية في الشركات الصناعية المدرجة في سوق عمان المالي - المحاميد، أسعود محمد فاضل; المصالحة، بلال سليمان محمد (جامعة مؤتة, 2016)
This study aimed to identify the impact of knowledge management operations practices on organizational agile capabilities in listed manufacturing companies in Amman Stock Exchange. In order to achieve the goal of the study, a private questionnaire was developed to collect data from the study sample. The population of this study consisted of all directors and heads departments of human resource management, research and development, and production (234) working at listed manufacturing companies in Amman Stock Exchange. A random sample that consists of (146) managers and heads of department were chosen. Among the most prominent findings the study arrived to are the listed manufacturing companies in Amman Stock Exchange practeizing knowledge creation and aqusition, knowledge retrival and documentation, knowledge sharing, knowledge application operations of a medium degree. The listed manufacturing companies in Amman stock exchange have organizational agile capabilities of a medium degree. The results also show the existence of a positive significant statistical impact for knowledge management operations practices on organizational agile capabilities. The study found that knowledge application process is the most influential in the organizational agile capabilities but the least influential is knowledge creation and aqusition process. Among the most prominent recommendations is the necessity for listed manufacturing companies in Amman stock exchange to activate the practices of various knowledge management operations to increase the speed of response to changes in business environment.
تهدف هذه الدراسة إلى التعرف إلى أثر ممارسة عمليات إدارة المعرفة في قدرات الذكاء التنظيمي في الشركات الصناعية المدرجة في سوق عمان المالي. ولغايات تحقيق هدف الدراسة تم تطوير استبانة خاصة لجمع البيانات من عينة الدراسة. ويتكون مجتمع الدراسة من جميع مديري ورؤساء أقسام الموارد البشرية، والبحث والتطوير، والإنتاج (البالغ عددهم 234) في الشركات الصناعية المدرجة في سوق عمان المالي، حيث تم اختيار عينة عشوائية مقدارها (146) مديراً ورئيس قسم. ومن أبرز النتائج التي توصلت إليها الدراسة إن الشركات الصناعية المدرجة في سوق عمان المالي تمارس عمليات خلق واكتساب المعرفة، تخزين وتوثيق المعرفة، ومشاركة المعرفة وتطبيق المعرفة بدرجة متوسطة. كما تمتلك الشركات الصناعية المدرجة في سوق عمان المالي قدرات ذكاء تنظيمي بدرجة متوسطة. كما بينت النتائج وجود أثر إيجابي ذي دلالة إحصائية لممارسة عمليات إدارة المعرفة في قدرات الذكاء التنظيمي. ووجدت الدراسة إن عملية تطبيق المعرفة هي الأكثر تأثيراً في قدرات الذكاء التنظيمي لكن أقلها خلق واكتساب المعرفة. ومن أبرز التوصيات ضرورة تفعيل الشركات الصناعية المدرجة في سوق عمان المالي لممارسة عمليات إدارة المعرفة المختلفة لزيادة سرعتها في الاستجابة للتغيرات الحاصلة في بيئية عملها.
Keywords: سوق عمان المالي -- الشركات الصناعية -- إدارة المعرفة -- التنظيم الإداري